PEDAGOGICAL VIEWS OF THE JADID ENLIGHTENMENT (Proceedings of International Educators Conference, 2024)
This thesis consists in studying the pedagogical theories of the Great Jadidists, their special methodologies, which left a deep mark on evolution of Turkestan. In addition, it is considered how many pedagogical views of these theories play an important role in our life.